Father and Daughter across Europe: The Journeys of Clara Wieck Schumann and Artemisia Gentileschi in Fictionalised Biographies - Julia Lajta-Novak (European Journal of Life Writing, 2012)
German pianist Clara Wieck Schumann and Italian painter Artemisia Gentileschi were both tutored by their fathers from an early age and made their mark as great European artists. Their art took them both across the continent, where they met many other famous historical persons. Their lives have not only been recorded in biographies but have also been retold in several novels, or ‘fictionalised biographies’. The fictionalised biography is an interesting hybrid genre, placed somewhat uncomfortably between historiography and the art of fiction, which permits it to disregard certain expectations raised by so-called ‘factual’ biographies (e.g. that authors should strive for ‘objectivity’ or ‘truthfulness’). The relationship between fact and fiction can thus be re-negotiated, following the author’s ideological inclinations and their imaginative closure of historiographical gaps. Beginning with some general remarks on fictionalised biographies of ‘exemplary women’, this paper then examines Janice Galloway’s Clara (2002) and Susan Vreeland’s The Passion of Artemisia (2002), focusing on the complex father-daughter relationships that Clara Wieck Schumann and Artemisia Gentileschi undoubtedly experienced, and which offered the authors ample ground for a critique of historical gender relations and hierarchies. The analyses will concentrate on the heroines’ journeys in Europe. The paper examines the ways in which the two fictional rewritings of historical women artists’ lives foreground gender aspects and make use of the narrative privileges of fictionalised biography to project contemporary feminist ideas onto historical characters and events, and explores the function of the featured European locales with regard to the protagonists’ personal development in the novels.The heroines’ ventures into foreign lands are revealed to function as an impulse towards a changing perception of their fathers as well as themselves.